2012
DOI: 10.1016/j.jcrs.2012.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of axis orientation on visual performance in astigmatic eyes

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 26 publications
7
51
2
Order By: Relevance
“…Oblique axis astigmatism has been associated with poorer visual performance than WTR or ATR astigmatism. 25,26 Our J45 regression slope results are similar to the findings of Tong et al 16 and Huynh et al 21 Relation Between Change in Keratometric Astigmatism and Change in Internal Astigmatism With Age…”
Section: Relation Between J45 Keratometric Astigmatism and J45 Internsupporting
confidence: 89%
“…Oblique axis astigmatism has been associated with poorer visual performance than WTR or ATR astigmatism. 25,26 Our J45 regression slope results are similar to the findings of Tong et al 16 and Huynh et al 21 Relation Between Change in Keratometric Astigmatism and Change in Internal Astigmatism With Age…”
Section: Relation Between J45 Keratometric Astigmatism and J45 Internsupporting
confidence: 89%
“…In this sense, a number of studies have not found a strong effect of induced cylinder axis on the changes in VA with astigmatism 19, 20, 21, 22, 23, 30. However, other studies have reported that ATR induced a greater reduction in VA compared to with WTR astigmatism6, 8, 24, 25, 26, 27, 28 and vice versa 25 . Methodological differences in terms of how astigmatism was simulated (with a cross-cylinder, pure positive cylindres, etc.)…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, in the description of a surgical method for optimizing the outcomes of refractive surgery, Alpins 26 also assumed that WTR astigmatism has a greater optical tolerance than ATR or oblique astigmatism. Kobashi et al 27 reported that oblique astigmatism had lower VA and reading performance than those with uncorrected 0° and 90° axis of astigmatism. Atchinson et al 8 found that subjective blur-limits for cylinder at 0° axis, were greater (about 20%) than those for oblique axes.…”
Section: Introductionmentioning
confidence: 99%
“…The current cases with WTR astigmatism in the non-toric group had less residual refractive cylinder compared to the cases with ATR astigmatism. Some studies have reported less of an effect on VA in cases with WTR astigmatism [14,15]. A recent study of posterior astigmatism reported the amount of overestimated cylinder when the anterior astigmatism is measured in cases with WTR astigmatism and underestimated in cases with ATR astigmatism, and a new nomogram was recommended [16,17].…”
Section: Discussionmentioning
confidence: 99%